Prevalence, Pattern and Predictors for Dyslipidemia of Chinese Women With Polycystic Ovary Syndrome - Luo, Xi; Cai, Wang-Yu; Wu, Xiao-Ke (Frontiers in Cardiovascular Medicine, 2021)
Objective: To investigate the prevalence, pattern and risk predictors for dyslipidemia among Chinese women with polycystic ovary syndrome (PCOS). Study Design and Methods: A total of 1000 women diagnosed as PCOS by modified Rotterdam criteria were enrolled in 27 hospitals across China in a randomized controlled trial. Anthropometric, metabolic parameters, sex hormone and lipid levels were measured at the baseline visit. Dyslipidemia was defined according to total cholesterol (TC), low density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C) and triglycerides (TG) level. Independent t-test and logistic regression were used to identify predictors for dyslipidemia. Area under the receiver operating characteristic curve (AUC) was calculated. Results: A total of 41.3% of the women had dyslipidemia, and the prevalence of abnormal TC, LDL-C, HDL-C and TG were 8.6%, 9.1%, 26.9%, 17.5%, respectively. Logistic regression found that age, waist circumference, insulin, follicle-stimulating hormone and sex hormone-binding globulin were independent predictors for dyslipidemia. When combining these predictors, the AUC was 0.744. The cut-off points were age > 28.5 years, waist circumference > 86.5 cm, insulin > 96.0 pmol/L, follicle-stimulating hormone < 5.6 mIU/mL, and sex hormone-binding hormone < 31.0 nmol/L, respectively. Conclusions: Dyslipidemia was common in Chinese women with PCOS, and low HDL-C level was the predominant lipid abnormality. Age, waist circumference, follicle-stimulating hormone and sex hormone-binding globulin were predictive for dyslipidemia among Chinese women with PCOS.